CÁC HỢP CHẤT TRITERPENOIT CỦA CÂY BỌT ẾCH (GLOCHIDION OBLIQUUM DECNE) Ở VIỆT NAM - Hoa, Lê Thị Mai; Hà, Lê Thị Thu; Thắng, Trần Đình (Vietnam Journal of Science and Technology, 2012)
CHEMICAL CONSTITUENTS OF GLOCHIDION OBLIQUUM FROM VIET NAM Five triterpenoids, euphorginol, taraxerol, 2a, 3a, 24-trihydroxyurs-12-en-28-oic acid, rotundic acid and pedunculoside were isolated from Glochidion obliquum (Euphorbiaceae) by column chromatography and identified by spectroscopic methods (UV, IR, MS, 1H-, 13C-NMR, DEPT, HMBC, HSQC, and COSY). These compounds were isolated from this plant for the first time.